CNS vasculitis and stroke as a complication of DOCK8 deficiency: a case report - AlKhater, Suzan A. (BMC Neurol, 2016)
BACKGROUND: Primary immunodeficiency disorders associated with autoimmunity are poorly understood. Central nervous system (CNS) vasculitis can complicate the courses of such entities, but it is underappreciated. Deletion of the dedicator of cytokinesis 8 (DOCK8) gene is considered to be the autosomal recessive form of hyperimmunoglobulin E syndrome which is a rare type of primary immunodeficiency disease characterized by elevated levels of IgE antibody, eczema, and recurrent staphylococcal infections. DOCK8 deletion is associated with fatal CNS vasculitis. However, descriptions of such cases and their outcomes are scarce in the literature. CASE PRESENTATION: This report describes a young female with a DOCK8 gene deletion presenting acutely with squint, fatigue and visual hallucinations. The patient was diagnosed as having neuritis of the third oculomotor nerve and encephalitis, which were thought to be related to her underlying immune deficiency, however, she subsequently was diagnosed with CNS vasculitis based on brain magnetic imaging and magnetic resonance angiography findings. We provide here a comprehensive description of the patient’s clinical outcome and outline an effective treatment approach that may be useful for similar patients and includes the use of steroids and mycophenolate mofetil (MMF). The treatment was well tolerated and enabled the patient to recover most of her neurological deficits. However, despite the initial improvement, she later developed stroke. CONCLUSIONS: To the best of our knowledge, this is the first report in the literature of a case of primary immunodeficiency complicated by CNS vasculitis demonstrating a successful outcome. Our observations indicate that the combination of MMF and steroids is an effective treatment for CNS vasculitis associated with DOCK8 deficiency. However, lack of awareness of the neurological comorbidities associated with primary immunodeficiencies and the delay in diagnosis likely contributed to the development of acute cerebral infarction. Early treatment and aggressive control of the disease’s initial inflammation is essential for preventing catastrophic stroke.